Unveiling the multifaceted dimensions: a sociological inquiry into kidnapping in Nigeria - Demehin, Michael Olusegun (Crime, law and social change, 2024)
One of the enduring social crimes throughout history is kidnapping. While its manifestations are global, there are distinct local variations in its specifics. This social malady has surged with alarming frequency, especially over the past decade in Nigeria, bringing with it significant impacts on the stability of the country. Thus, it becomes crucial to delve into its patterns, various occurrences, and to comprehend the theoretical foundations that underlie it. In order to uncover the sociological underpinnings of this crime, and the intertwined triggers, this study extensively reviewed relevant literature. The argument presented in this paper delineates the annals of kidnapping in Nigeria into two phases: the slavery and precolonial era, and the contemporary period. Triggers for kidnapping were analyzed and categorized into distinct clusters: an underlying cluster (socio-economic disparities, a dysfunctional law enforcement and judicial system, and longstanding conflicts); a remote cluster (political instability, the presence of militant groups, and insurgency); and an immediate cluster (vulnerable demographics, lack of robust security measures, and instances of diverse unrest). Moreover, the paper contends that the persistence of kidnapping is exacerbated by the flourishing economy it has spawned. Through an examination of theories associated with kidnapping, a comprehensive conceptual framework was developed, integrating the multifaceted factors relevant to the Nigerian context. It is anticipated that the findings of this study will contribute to the formulation of new policies, and the refinement of existing ones, aimed at fostering a safe, secure, and peaceful socioeconomic development.